2019
DOI: 10.1111/wre.12374
|View full text |Cite
|
Sign up to set email alerts
|

In‐field classification of herbicide‐resistant Papaver rhoeas and Stellaria media using an imaging sensor of the maximum quantum efficiency of photosystem II

Abstract: SummaryReliable in‐season and in‐field tools for rapidly quantifying herbicide efficacy in dicotyledonous weeds are missing. In this study, the maximum quantum efficiency of photosystem II (Fv/Fm) of susceptible and resistant Papaver rhoeas and Stellaria media populations in response to treatments with acetolactate synthase (ALS) inhibitors were examined. Seedlings (4–6 leafs) were transplanted into the field immediately after the application of the ALS inhibitors florasulam, metsulfuron‐methyl and tribenuron‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Other characteristics, such as fresh weight accumulation, seed production and capsule number of the resistant populations grown under field conditions, were similar to those recorded for the susceptible populations [88]. Another study examined early biochemical differences in the photosynthetic efficiency of photosystem apparatus (a light phase of photosynthesis) between biotypes of poppy susceptible and resistant to sulfonylurea herbicides, namely florasulam, metsulfuron-methyl and tribenuron-methyl [105]. It turned out that three days after herbicide spraying, the TSR population of poppy exhibited the maximum quantum efficiency of photosystem II (Fv/Fm) values similar to the untreated control, and these were about 20% higher than those of the sensitive plants in all herbicide treatments.…”
Section: Fitness Costs Of Herbicide-resistant Corn Poppymentioning
confidence: 63%
See 1 more Smart Citation
“…Other characteristics, such as fresh weight accumulation, seed production and capsule number of the resistant populations grown under field conditions, were similar to those recorded for the susceptible populations [88]. Another study examined early biochemical differences in the photosynthetic efficiency of photosystem apparatus (a light phase of photosynthesis) between biotypes of poppy susceptible and resistant to sulfonylurea herbicides, namely florasulam, metsulfuron-methyl and tribenuron-methyl [105]. It turned out that three days after herbicide spraying, the TSR population of poppy exhibited the maximum quantum efficiency of photosystem II (Fv/Fm) values similar to the untreated control, and these were about 20% higher than those of the sensitive plants in all herbicide treatments.…”
Section: Fitness Costs Of Herbicide-resistant Corn Poppymentioning
confidence: 63%
“…It turned out that three days after herbicide spraying, the TSR population of poppy exhibited the maximum quantum efficiency of photosystem II (Fv/Fm) values similar to the untreated control, and these were about 20% higher than those of the sensitive plants in all herbicide treatments. This characteristic could provide the basis for early in-field detection of TSR poppy [105].…”
Section: Fitness Costs Of Herbicide-resistant Corn Poppymentioning
confidence: 98%
“…Wang et al (2018) found significantly higher F v / F m values in resistant biotype of A. myosuroides than in the susceptible biotype at 3 days after treatment with ACCase, ALS and PSII inhibiting herbicides. Likewise, Linn et al (2019) successfully used the F v / F m parameter for the detection of herbicide resistant plants of Stellaria media L. Vill and Papaver rhoeas L. after ALS‐inhibiting herbicide treatment. The discrimination between susceptible and resistant plants was possible 3 DAT (three days after the treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Ballerina Forte, SE (complex 2-ethylhexyl ester of 2.4-D acid, 300 g/l, picloram, 37.5 g/l, and florasulam, 10 g/l.) is a herbicide with enhanced action used against perennial dicotyledonous and annual dicotyledonous weeds on grain crops and corn [6][7][8]. To determine the biological effectiveness of herbicides, we used the quantitative weight-related and quantitative methods of weed counting.…”
Section: Methodsmentioning
confidence: 99%